Evaluasi Pengaruh Geometri Jalan Angkut Terhadap Produktivitas Dump Truck Mitsubishi Fuso 220 PS dari Front Penambangan Menuju Unit Crusher pada Penambangan Batu Andesit PT Koto Alam Sejahtera - Fadhilah Maharani; Sumarya Sumarya (Journals Mining Engineering : Bina Tambang, 2018)
Abstract. PT Koto Alam Sejahtera located in Nagari Koto Alam, Pangkalan Koto Baru Subdistrict, Lima Puluh Kota District, West Sumatra Province. The production target of    PT Koto Alam Sejahtera is 30.000 tons / month, meanwhile the actual production is 16.965,6 tons / month. Based on observations, the road grade is still high, no cross slope is visible and two conveyances cant’t pass at the same time because the width on the road is narrow.This type of research is applied research by combining theory and field data to solve problems. The actual road width ranged is from 6,35-12,15 meters while theoretically is 9 meters. The actual bend road width ranges is from 6,20-12,70 meters while theoretically is 12 meters. Actual road grades range from 3,49%-19,44% while the ideal road grade is 8%. The cross slope value for the 9 meter road width is 0,04 and the height difference is 18 cm. The superelevation value for the 12 meter bend width is 0,04 and the height difference is 48 cm.There were 7 straight road width segments that needed to be added and 2 bend road width segments, and there are 8 segments that need to be downgraded. Productivity of Mitsubishi Fuso 220 PS with actual conditions of 16.965,6 tons / month. The estimated increase in the productivity of Mitsubishi Fuso 220 PS after an evaluation is 27.593,89. Theoretical productivity of Mitsubishi Fuso 220 PS after the improvement of work efficiency is 34.395,3 tons / month.Keywords:  Road Geometry, Production, Dump Truck, Work Efficiency, Cross Slope